Correlation of donor-acceptor pair emission on the performance of GaN-based UV photodetector. (1st August 2019) - Krishna, Shibin; Aggarwal, Neha; Gundimeda, Abhiram; Sharma, Alka; Husale, Sudhir; Maurya, K.K.; Gupta, Govind
Abstract: High responsivity UV photodetector has been realized by fabricating single crystalline epitaxial GaN-based devices grown on silicon substrate by using molecular beam epitaxy system. The influence of trap states existing within the forbidden gap on GaN-based optoelectronic devices has been investigated. The quality and performance of the fabricated GaN based UV photodetector with distinct AlN buffer layer grown at low and high substrate temperature are substantiated. A detailed analysis reveals that high temperature buffer can yield improved crystalline quality of GaN with similar morphological properties as compared to buffer layer grown at low temperature. However, the distinct buffer layer influence the optical properties as the photoluminescence analysis explains that both the films possess superior band-to-band edge emission where GaN grown with high temperature AlN buffer consists of dominant acceptor defect states in comparison to GaN with low temperature AlN buffer layer. The existence of acceptor states has been accredited by the presence of Ga vacancy related states in the band gap. The fabricated devices yield high photoresponsivity of 2.1 and 1.5 A/W at 1 V from GaN films bearing low and high accepter defect states which explain a clear correlation of device performance with trap states within the band-gap region.